Enhancing the Conductivity and Dielectric Characteristics of Bismuth Oxyiodide via Activated Carbon Doping - Mohamed Khairy; Faisal K. Algethami; Abdullah N. Alotaibi; Rasmiah S. Almufarij; Babiker Y. Abdulkhair (Molecules, 2024)
Activated carbon/BiOI nanocomposites were successfully synthesized through a simplistic method. The produced composites were then characterized using XRD, TEM, SEM-EDX, and XPS. The results showed that BiOI with a tetragonal crystal structure had been formed. The interaction between activated carbon and BiOI was confirmed via all the mentioned tools. The obtained nanocomposites’ electrical conductivity, dielectric properties, and Ac impedance were studied at 59 KHz−1.29 MHz. AC and dc conductivities were studied at temperatures between 303 and 573 K within the frequency range of 59 KHz–1.29 MHz. The 10% activated carbon/BiOI nanocomposite possessed dc and AC conductivity values of 5.56 × 10−4 and 2.86 × 10−4 Ω−1.cm−1, respectively, which were higher than BiOI and the other nanocomposites. Every sample exhibited increased electrical conductivity values as the temperature and frequency rose, suggesting that all samples had semiconducting behavior. The loss and dielectric constants (ε′ and ε″) also dropped as the frequency increased, leading to higher dielectric loss. The Nyquist plot unraveled single semicircle arcs and a decreased bulk resistance, indicating decreased grain boundary resistance. Consequently, the electrical characteristics of BiOI, 1C/BiOI, 5C/BiOI, and 10C/BiOI implied their applicability as dielectric absorbers, charge-stored capacitors, and high-frequency microwave devices.